Implementasi Algoritma Complementary Filter untuk Merancang Bangun Interaksi Manusia dan Smartphone Menggunakan Gerakan Kepala - Pingky Alfa Ray Leo Lede (Politeknik Negeri Jakarta, 2020)
This study proposes an approach to design and build interaction systems for smartphone users with hand disabilities using the user's head movements through the implementation of the fusion complementary filter algorithm to get the angle of orientation and position of the user’s head. The main objective of this experimental research is to get the best constant function of complementary filters that have the highest accuracy result. The results of this study indicate that the fusion complementary filter algorithm can be used to measure the angle of the user's head movements using a combination of 3 sensors; namely, the accelerometer, gyroscope, and magnetometer, with the best constants function are 0.99 for the gyroscope and 0.01 for the accelerometer. Complementary filter performance results using fusion of 3 sensors to measure the user's head angle obtained from the calculation of the root mean squared error (RMSE) with an average value of 0.364 on the x-axis (roll), 0.578 on the y-axis (pitch), and 0.767 on the z-axis (yaw).